2021
DOI: 10.15541/jim20210030
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Mineralization Property of Borosilicate Bioactive Glass under DC Electric Field

Abstract: Borosilicate bioactive glass has excellent bioactivity and bone conductivity, but most bioactive glasses exhibit nonlinear degradation and mineralization behavior, with mineralization property declining over time. The DC electric field, as an outfield-assisted approach to regulation, can interfere in the ion exchange and diffusion of the glass to modify its property. In this study, a DC electric field is used to intervene in vitro mineralization of borosilicate bioactive glass to accelerate the bioactivity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The DC stimulation of osteogenesis may be related to electrochemical reactions occurring at the electrodes, such as changes in oxygen partial pressure and pH [ 33 ]. In the previous study, we found that applying a DC electric field can improve the degradation and mineralization of a borosilicate bioactive glass [ 34 ]. However, the mechanism by which the DC electric field affects the degradation of the glass is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The DC stimulation of osteogenesis may be related to electrochemical reactions occurring at the electrodes, such as changes in oxygen partial pressure and pH [ 33 ]. In the previous study, we found that applying a DC electric field can improve the degradation and mineralization of a borosilicate bioactive glass [ 34 ]. However, the mechanism by which the DC electric field affects the degradation of the glass is unclear.…”
Section: Introductionmentioning
confidence: 99%